ANALISA PERATURAN DAERAH KABUPATEN BANTUL TENTANG MITIGASI BENCANA - , KURNIA SARI DEWI WIJAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Disasters can happen anytime and anywhere, therefore pre-disaster mitigation is needed. Learning from the earthquake in Bantul 2006 on the importance of mitigation, which never been done before. One form of mitigation is the establishment of disaster-related regulations. Especially at the central level has been established Law No.24 of 2007 on Disaster Management. Bantul local regulation number 05 of 2010 on disaster management also has been established in Bantul. Regulations need to be proven itâs substance about mitigation, about the authority of each agency in mitigation and how the implications of regulation towards mitigation in Bantul. This is done because there are some regulations, and some of the agencies that participated in mitigation that are appropriated to their respective fields. The method used in this research is descriptive qualitative method. Data collection method useing interviews, documentaries and online-data seeking. Data source in form of regulations are sorted and filtered according to the research focus. Informants are picked and choosen based on focus of the research. The data that has been collected have to got analyzed with another data in order to make the data can be understood easily. The results of the analysis showed that there were some regulations on mitigation that become reference for Bantul local government and Regional Work Unit in Bantul, be it the laws and regulations that applied at the central level or at the regional level Bantul local government Regional Work Unit in Bantul local government that involved in mitigation include: Local Body for Disaster Management, Health Department, Social Service Department, Department of Public Work and Department of Middle and Non-Formal Education. Each Region Work Unit refers to the regulations that appropriate with their respective areas of expertise. Regulations that applied in Bantul include chapters about mitigation. The articles about the mitigation that has been applied is still general, not too specific. From the discussion that has been done, the division of authorit about mitigation in Bantul approriate with their respective expertise. The implication of regulations that has been the foundation of mitigation in Bantul can be seen in mitigation activities in Bantul. Recommendations to be considered with regard to the substance of the regulations. Most regulations that are established are still too general to explain mitigation, moreover the field of mitigation is different one another. Therefore, substance of mitigation need to be clarified so that the implementation of mitigation is appropriate with the regulations.